Stomach Content Analysis of HampalamacrolepidotaKuhl& Van Hasselt, 1823 from the Kampar KiriRiver, Mentulik Village, KamparKiri HilirDistrict, Kampar Regency, Riau Province - G Manurung, Popy; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractHampalamacrolepidota is a carnivorous  fish that inhabit the Kampar Kiri River, Mentulik Village. In the Kampar Kiri River there is waste from illegal gold mining, domestic waste, and floating cage aquaculture activities that pollute the water. The pollution may negatively affects small aquatic organisms that represent as prey for H. macrolepidota.To understand the type of food consumed by H. macrolepidota, a study has been conducted from  February to April 2018. Sampling was conducted 4 times, once/ 2 weeks for a two months period. There were 52 fishes captured, 19 fishes had full stomach and the others had empty stomach. Fish stomach was dissected, and each type of stomach contents was identified and weighed.Results shown that the content of the fish stomach consists of fish, leaves, and insect remains. The main food of H. macrolepidota is fish (Preponderance Index 90%).Keyword:Cyprinidae, Feeding Habit, Index of Preponderance, Carnivore fish.